The Philippine View of Indonesian Independence: As Reported in Philippine Newspapers - Augusto V. De Viana (Jurnal Kajian Wilayah, 2013)
For the Filipinos, seeing Indonesia become independent was like seeing themselves. Filipinos themselves as inspiring their neighbors and at the same time they saw what their country could be. There are various parallelisms not only on the day Indonesia formally entered the community of nations but also through that nations struggle for freedom and independence. Here the Filipinos can see the various paths they may have taken, an armed struggle or a peaceful political negotiation, or both. Indonesians too saw themselves among the Filipinos. Like many Asians, they observed events from the 19th century to the recognition of Philippine sovereignty by the United States. At the same time, both countries entered a neocolonial period with the Philippines entering various agreements with its former colonizer which tied up its prerogatives. The Hague Agreement tried to impose a neocolonial condition by constructing a Netherlands-Indonesian union similar to that of the British Commonwealth of Nations. At the same time, the Netherlands played an old tactic of divide and rule by setting up what appeared to be puppet governments in the various regions of Indonesia in support for itself and denying Indonesia the western part of New Guinea by alleging that the region was not culturally affiliated with the central and western halves of the archipelago. It was an attempt to retain the Netherlands as an Asian power. Like the Philippines Indonesia faced new challenges after independence and most of these involved its former colonizer.